2019
DOI: 10.1021/acs.jpca.9b10808
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the Drop-Weight Impact Sensitivity of Common Explosives Using Arrhenius Chemical Rates Computed from Quantum Molecular Dynamics Simulations

Abstract: Drop-weight impact tests are used routinely to characterize the handling safety of explosives. Numerous studies have sought to connect various physical and chemical properties of the energetic molecules and materials to their measured impact sensitivities. Wenograd in the early 1960s demonstrated that there is a strong dependency of the drop-heights on the critical temperatures required for explosives to undergo prompt reactions. Reactive quantum molecular dynamics simulations with the lanl31 density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 64 publications
0
42
2
Order By: Relevance
“…Previous drop-weight impact test results with DAAF have indicated that the explosive is quite insensitive to a nonshock-induced impact, with drop heights at the upper limit of the test (>320 cm) . However, in recent drop-weight testing by the authors, DAAF exhibited DH 50 values (the height from which 50% of the drops exhibited an audible “go”) at significantly lower values than those previously recorded . Higher DH 50 values correspond to more energy required to generate a reaction, or “go”, using sound meters.…”
Section: Results and Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Previous drop-weight impact test results with DAAF have indicated that the explosive is quite insensitive to a nonshock-induced impact, with drop heights at the upper limit of the test (>320 cm) . However, in recent drop-weight testing by the authors, DAAF exhibited DH 50 values (the height from which 50% of the drops exhibited an audible “go”) at significantly lower values than those previously recorded . Higher DH 50 values correspond to more energy required to generate a reaction, or “go”, using sound meters.…”
Section: Results and Discussioncontrasting
confidence: 67%
“…In contrast, we have observed that DH 50 values for PETN and other standard explosives typically increase on the bare anvil relative to the values collected using grit. 6,60 Sound level data for each impact test drop of DAAF and HMX can be seen in Table 3 and Figure 5, where the sound threshold for a "go" is represented by the horizontal lines in each plot. The plots with HMX have a clearly defined separation between a "go" (above 117 dB) and a "no go" (well below 117 dB) with better separation apparent in the gritcontaining samples, likely due to reliable sources of ignition through friction in those samples.…”
Section: Drop-weight Impact Testsmentioning
confidence: 99%
See 3 more Smart Citations